Live Epidemiological Tracking of COVID-19 in Senegalese Participants of the Hajj - Dr. Aminata Mboup; Abdou Padane; Dr. Yacine Amet Dia; Mr. Seyni Ndiaye; Dr. Marièma Sarr; M. Marilyne Aza-Gnandji; Mr. Mamadou Ndao; Mr. Abdoulaye Samba Diallo; Mr. Ousmane Diop; Mr. Bacary Dembo Diatta; Mr. Ousmane Diouf; Mr. Abdoulaye Leye Sarr; et al. (Recent Trends in Infectious Diseases, 2025)
Background: Since the COVID-19 outbreak, global efforts have focused on controlling the disease. However, intense cross border movements pose a risk for the emergence of new SARS-CoV-2 strains. A recent example is the detection of cases among the 2024 Senegalese pilgrims returning from Mecca, Saudi Arabia. Investigations of these cases have revealed genomic evolution of the virus. The lack of surveillance may lead to the emergence of high-threat strains. This study aims to identify new SARS-CoV-2 emerging lineages isolated from returning Senegalese Pilgrims. Methods: Whole Genome Sequencing, using midnight protocol on ONT platform, has been used to characterize SARS-CoV-2 strains isolated from pilgrims. An integrated approach, involving strong collaboration with the Ministry of Health (MoH), was utilized for data sharing with patients and healthcare authorities. Results: Among 66 positive samples sequenced with coverage ≥ 80%, we detected the presence of the JN.1 sub-lineage (47.5%) and the emergence of the JN.1.18 variant (3.27%). In addition, JN.1.18.3 (21.311%) had many mutations more than JN.1. The other variants, LF.1.1.1 (6.56%), JN.1.16 (1.56%), JN.1.18.2 (1.64%), KP.1.1.1 (4.91%), KP.1.1.3 (3.27%), LP.2 (3.27%). LB.1.4 (4.91%), and KS.1.1 (1.645%) have never been identified in Africa. New lineages LS.1 (2.54%) and JN.1.18.5 (3.27%) were identified in real time during this intervention. Conclusion: It is important to monitor the emergence of new variants among pilgrims and the general population, as well as the clinical course of patients, to determine the virulence of these variants.
Keywords: COVID-19; Genomic Surveillance; New lineages; Pilgrims; Sars-CoV-2; Senegal